DI BALIK TRADISI BAANTARAN JUJURAN: Simbol dan Makna Perkawinan Adat Banjar dalam Perspektif Hukum Islam - Humaira; Nasrun Jauhari (Usrotuna: Journal of Islamic Family Law, 2025)
The Baantaran Jujuran procession constitutes an essential element in the sequence of Banjar customary marriage rituals, which continues to be preserved and regarded as sacred as part of ancestral heritage. This tradition embodies cultural symbols that carry significant social functions and normative values, while Banjar society, predominantly Muslim, adheres to Islamic law as the principal guideline in the implementation of marriage. This study aims to analyze the symbols and meanings embedded in the Baantaran Jujuran procession and to examine its legal standing within Banjar customary marriage from the perspective of Islamic law. This research employs a qualitative method with a descriptive-analytical approach, drawing upon library research and relevant field data, framed within an Islamic legal analysis based on the concept of ‘urf and the principle of maslahah. The findings indicate that the symbols present in the Baantaran Jujuran procession consistently appear in every Banjar customary marriage and function as representations of respect, responsibility, and the readiness of the prospective groom to establish a household. This tradition serves not merely as a ceremonial ritual but also as a social mechanism that strengthens kinship relations and provides social legitimacy to the marriage. The study concludes that the Baantaran Jujuran procession may be classified as ‘urf ṣaḥīḥ, as it does not contradict the principles of Islamic law and contains values of maslahah that are relevant to the objectives of marriage in Islam. Contribution: The contribution of this research lies in strengthening Islamic legal studies grounded in local wisdom, while also offering an analytical framework for integrating customary traditions with Islamic normative principles in the marital practices of Muslim communities. [Tradisi prosesi baantaran jujuran merupakan bagian penting dalam rangkaian perkawinan adat Banjar yang hingga kini masih dilestarikan dan dipandang sakral sebagai warisan leluhur. Tradisi ini mengandung simbol-simbol budaya yang memiliki fungsi sosial dan nilai normatif, sementara masyarakat Banjar secara mayoritas beragama Islam yang menjadikan syariat sebagai pedoman dalam pelaksanaan perkawinan. Penelitian ini bertujuan untuk menganalisis simbol dan makna yang terkandung dalam prosesi baantaran jujuran serta menilai kedudukannya dalam perkawinan adat Banjar dari perspektif hukum Islam. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif-analitis, melalui studi kepustakaan dan data lapangan yang relevan, dengan kerangka analisis hukum Islam berbasis konsep ‘urf dan prinsip kemaslahatan. Hasil penelitian menunjukkan bahwa simbol-simbol dalam prosesi baantaran jujuran secara konsisten hadir dalam setiap pelaksanaan perkawinan adat Banjar dan berfungsi sebagai representasi penghormatan, tanggung jawab, serta kesiapan calon pengantin laki-laki dalam membangun rumah tangga. Tradisi ini tidak hanya berperan sebagai ritual seremonial, tetapi juga sebagai mekanisme sosial yang memperkuat relasi kekeluargaan dan legitimasi sosial perkawinan. Kesimpulan penelitian ini menunjukkan bahwa prosesi baantaran jujuran dapat dikategorikan sebagai praktik ‘urf ṣaḥīḥ karena tidak bertentangan dengan prinsip-prinsip syariat Islam dan mengandung nilai kemaslahatan yang relevan dengan tujuan perkawinan dalam Islam.] Kontribusi: Kontribusi penelitian ini terletak pada penguatan kajian hukum Islam berbasis kearifan lokal, sekaligus memberikan kerangka analitis bagi integrasi antara tradisi adat dan norma syariat dalam praktik perkawinan masyarakat Muslim.